2020
DOI: 10.1097/brs.0000000000003521
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Decompression Effect to Central Canal and Ligamentum Flavum After Extreme Lateral Lumbar Interbody Fusion and Oblique Lumbar Interbody Fusion

Abstract: Study Design. A retrospective study (level of evidence: level 4). Objective. To evaluate the radiographic outcomes after extreme lateral lumbar interbody fusion (XLIF) and oblique lateral lumbar interbody fusion (OLIF) procedures especially the effect of indirect decompression to the ligamentum flavum and to evaluate the effect of facet degeneration to the radiographic outcomes of these procedures. Summary of Background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 16 publications
3
39
0
2
Order By: Relevance
“…OLIF as an indirect neural decompression had a satisfactory clinical outcome for degenerative spine disease [19,27,36]. The current study had similar results with previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…OLIF as an indirect neural decompression had a satisfactory clinical outcome for degenerative spine disease [19,27,36]. The current study had similar results with previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding that expansion of DH associated with an increment in central canal decompression was supported by previous studies. The multivariate analysis showed that cage morphology and position were not associated with the percentage change of SCSA, similar conclusions were reported 11,12,21) .…”
Section: Factor Associated With Central Spinal Canal Decompressionsupporting
confidence: 83%
“…To the authors' knowledge, this complication has not been reported and discussed. Numerous studies have described the powerful phenomenon of indirect decompression of the neural elements using lateral or anterior interbody cages [16][17][18]. The reports describe Case Reports in Orthopedics how interbody cages can increase disk height, foraminal height, and cross-sectional area of the spinal canal and foramina.…”
Section: Discussionmentioning
confidence: 99%